Metabolic engineering of the thermophile Geobacillus to produce the advanced biofuel N-butanol - Spencer, Jennifer (2018)
Limited fossil fuel resources and the environmental impacts of climate change are motivating the development of sustainable processes for the production of fuels and chemicals from renewable resources. The development of alternative energy sources, such as biofuels, will strengthen energy security and reduce dependence on fossil fuels. n-butanol is a biofuel and platform chemical. n-butanol is an advanced fuel with high energy content, compatible with existing infrastructure. Here the ability of microorganisms to use renewable resources for biofuel synthesis is exploited. In this work use of the thermophilic bacterium Geobacillus thermoglucosidasius is explored for the production of n-butanol. Geobacillus is considered a promising industrial process organism due to its high optimum growth temperature and ability to assimilate various substrates including both hexose and pentose sugars. As a relatively novel process organism, first the development of molecular tools was required to enable subsequent engineering of the host metabolism. Here four reporter assays were developed, three of which can be used simultaneously, providing for extensive analysis of qualitative and quantitative gene expression within the cell. A range of promoters and RBS’ were screened. Extension of the Geobacillus vector series, pMTL60000, with new component parts for each module enabled co-transformation of two plasmids into G. thermoglucosidasius. The molecular tools developed were then applied in Geobacillus metabolic engineering work, with the aim of producing the target molecule n-butanol. Initially a CoA dependent n-butanol pathway, based on naturally occurring production by ABE fermentation, was considered. Following introduction of the pathway further metabolic engineering was employed to improve pathway flux, creating a driving force through the pathway and increasing the substrate pool. Production of 0.137 mM (10.166 mg/l) n-butanol demonstrated proof of concept. Next, the use of genes native to Geobacillus were investigated for improved enzyme compatibility. This approach did not generate n-butanol here. Finally a CoA independent pathway utilising the host’s native fatty acid biosynthesis pathway was considered. Using this approach, butyric acid was produced. Butyric acid can subsequently be further converted to n-butanol however this was not demonstrated here. In addition to metabolite pathway introduction, host strain engineering was carried out with the aim of adaptation towards industrially desired properties. Directed evolution resulted in selection of a strain with an increased n-butanol tolerance of 2.5% (v/v). Such modifications resulted in an improved process organism for biotechnological application.